2004
DOI: 10.1007/s00213-004-1894-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the antidepressant nefazodone on the density of cells expressing mu-opioid receptors in discrete brain areas processing sensory and affective dimensions of pain

Abstract: Therefore, chronic nefazodone induces antinociceptive and antidepressant-like effects in rats and increases mu-opioid receptor expression in brain areas related to pain and affective state. These results suggest that antidepressants could be effective on somatic and affective dimensions of pain and this action could be related to its influence on the opioid system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Some studies on the acute or sub-chronic action of antidepressant drugs showed that opioid antagonists can block the antidepressant-induced analgesia (Reichenberg et al, 1985;Valverde et al, 1994;Gray et al, 1998;Su and Gebhart, 1998;Schreiber et al, 1999Schreiber et al, , 2002Marchand et al, 2003c;Ortega-Alvaro et al, 2004;Mico et al, 2006;Benbouzid et al, 2008a,b), suggesting the involvement of the opioid system. On the contrary, other studies showed no effect of opioid antagonists on antidepressant drug action (Pick et al, 1992;Fuchs et al, 1996;Ghelardini et al, 2000;Marchand et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on the acute or sub-chronic action of antidepressant drugs showed that opioid antagonists can block the antidepressant-induced analgesia (Reichenberg et al, 1985;Valverde et al, 1994;Gray et al, 1998;Su and Gebhart, 1998;Schreiber et al, 1999Schreiber et al, , 2002Marchand et al, 2003c;Ortega-Alvaro et al, 2004;Mico et al, 2006;Benbouzid et al, 2008a,b), suggesting the involvement of the opioid system. On the contrary, other studies showed no effect of opioid antagonists on antidepressant drug action (Pick et al, 1992;Fuchs et al, 1996;Ghelardini et al, 2000;Marchand et al, 2003a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants can interact with the opioid system, thus affecting pain-related processes [1] . Results of the present investigations allow to conclude that adrenergic stimulation at least prolonged the fentanyl analgesia since this effect was observed after amitriptyline, moclobemide and reboxetine ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the administration of antidepressants increases opioid receptor density in brain areas implicated in pain and depression (Ortega-Alvaro et al, 2004;Reisine & Soubrie, 1982). For example, chronic citalopram administration increases naloxone binding in cortical membranes (Antkiewicz-Michaluk et al, 1984), while imipramine and fluoxetine increase neuronal μ-opioid receptor expression in the prefrontal cortex, hippocampus and caudate putamen (de Gandarias et al, 1999;.…”
Section: The Opioid Systemmentioning
confidence: 99%
“…Most evidences indicate the involvement of ionic channels (such as calcium, potassium and sodium) and neurotransmitter receptors (gamma-aminobutyric acid or GABA, N-methyl-D-aspartate, or NMDA and substance P) in the analgesic mechanism of action of antidepressants. It is interesting to note that among antidepressants, TCAs are those that act on multiple nociceptive targets both at central and Venlafaxine Nomifensine Nefazodone Mirtazapine Mianserin (Gray et al, 1998;Hamon et al, 1987;Marchand et al, 2003;Ortega-Alvaro et al, 2004;Schreiber et al, 1999;Schreiber et al, 2002;Valverde et al, 1994)(Cai & McCaslin, 1992;Eisenach & Gebhart, 1995;Mjellem et al, 1993;Skolnick et al, 1996;Su & Gebhart, 1998) ↓ Substance P peripheral levels (Table 3) and this may be the reason why TCAs seem to be more effective than other antidepressants with a more selective monoaminergic mechanism of action. For example, many actions have been described for amitriptyline: blocking NMDA receptors and sodium channels (Sudoh et al, 2003).…”
Section: Other Mechanisms Involvedmentioning
confidence: 99%